The persistence of the caliphate debate in Egyptian legal thought: Historical analysis from 1925 to 2014 - Salem, Assil (AUC Knowledge Fountain, 2015)
In the early centuries of Islam, the term caliph was referred to the highest leader of the Muslim community. He had two roles; firstly as a ruler practicing the roles of the Prophet and secondly as a religious leader leading the communal prayers. The Caliphate has appeared for fourteen centuries and was abolished by Mustafa Kemal Atātūrk in 1924. Although Muslims have been without caliph for ninety years, heated controversy on the restoration of the Caliphate has been debated among Egyptians since 1920s until 2015. This thesis aims to answer the caliphate question,” is the Caliphate obligatory in Shari’a?” by conducting a historical analysis of the views of six sunni scholars and the group of Islam State of Iraq and Syria (ISIS) on the caliphate from 1920s to 2014. Two of the six sunni scholars, ‘Alī ‘Abdal Rāziq and Nasr Hāmyd Abū Zayd argued that the Caliphate had no foundations neither in the Qur’an nor Sunna. The other sunni scholars, ‘Abdal -Rāziq al-Sanhūrī, Muhammad ‘Imāra, Hasan al-Banā, Ibn Taymiyya and ISIS believed in the obligation of the Caliphate in Shari’a.